G327(P) Children and young people seen in a co-located primary care hub; an observational study. (May 2019) - James, D; Kithany, H; Robbins, A; Crouch, R
Abstract : Aim: Emergency Department (ED) visits have increased by 35% in the last decade with 30% potentially manageable in primary care. Our aim was to evaluate the impact on children and young people of a newly opened co-located Primary Care Hub (PCH) alongside the ED. Patients presenting to ED are streamed to the hub provided they do not meet any of the set age/clinically defined exclusion criteria. Methods: Data was collected from 1/10/17 – 31/12/17 (3 months). Retrospective case note analysis was performed using the 'System One' IT system for all children and young people seen in the primary care hub during its opening times (Monday-Friday 1800–2200, Saturday-Sunday 1100–2200). This was compared with children and young people seen in the ED outside these times using the 'Symphony' IT system. The ED group were searched using the same exclusion criteria used at streaming to exclude redirection to the primary care hub (<3 months old with fever, accidental poisoning, injuries, mental illness, previous ED within last 72 hours, suspected sepsis) Results: 336 children and young people were seen in the PCH with 1438 matched patients seen in ED. Mean time in the department for patients seen in the PCH was lower than in ED (1 hour 19 minutes v 2 hours 45 minutes p<0.01). Investigation rate was lower for those seen in the PCH ((5/336 (1.48%) v 77/1338 (5.75%) p0.01). A higher proportion of those seen in the PCH received drugs to take home than those seen in ED ((124/336 (36.80%) v 236/1338 (17.64%) p<0.01). The most commonly prescribed drugs were antibiotics, bronchodilators and analgesia for both groups. Discussion: Initial experience of a co-located Primary Care Hub model demonstrated significant benefits in waiting times as well as demonstrating a lower rate of investigation. It highlighted a significantly higher prescribing rate, though more work is needed to understand the exact prescribing patterns involved. This demonstrates the potential for shared learning across both services. Further work is needed to study patient experience before recommending its wider expansion and implementation.